1992
DOI: 10.1093/oxfordjournals.jbchem.a123706
|View full text |Cite
|
Sign up to set email alerts
|

Fast Skeletal Myosin Isoforms in Thermally Acclimated Carp1

Abstract: Fast skeletal myosins were isolated from carp acclimated to 10 and 30 degrees C, and their structural and enzymatic properties were compared. Myosins in 0.5 M KCl were subjected to limited proteolysis by using various proteases including alpha-chymotrypsin, trypsin, and papain, and different SDS-PAGE patterns were seen for the 10- and 30 degrees C-acclimated myosins in all cases. Myosin subfragment-1 (S1) prepared from the 10 degrees C-acclimated myosin by alpha-chymotryptic digestion in 0.12 M NaCl showed hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

1993
1993
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 58 publications
(32 citation statements)
references
References 27 publications
0
32
0
Order By: Relevance
“…In several species, fast-start performance and maximum sustained swimming speed at low and high temperatures are increased in response to cold and warm acclimation, respectively (reviewed in Johnston and Temple, 2002). The mechanisms are complex, but can include a significant remodelling of the sarcoplasmic reticulum and marked changes in the expression of contractile protein isoforms including the myosin II gene family (Watabe et al, 1992;Johnston and Temple, 2002). Fast myotomal muscle in medaka (Oryzias latipes) differentially expresses eight active myosin heavy chain genes at particular acclimation temperatures, a process potentially controlled by MEF2 family members (Liang et al, 2008).…”
Section: Plasticity Of the Myogenic Phenotypementioning
confidence: 99%
“…In several species, fast-start performance and maximum sustained swimming speed at low and high temperatures are increased in response to cold and warm acclimation, respectively (reviewed in Johnston and Temple, 2002). The mechanisms are complex, but can include a significant remodelling of the sarcoplasmic reticulum and marked changes in the expression of contractile protein isoforms including the myosin II gene family (Watabe et al, 1992;Johnston and Temple, 2002). Fast myotomal muscle in medaka (Oryzias latipes) differentially expresses eight active myosin heavy chain genes at particular acclimation temperatures, a process potentially controlled by MEF2 family members (Liang et al, 2008).…”
Section: Plasticity Of the Myogenic Phenotypementioning
confidence: 99%
“…The chymotryptic fragments of myosin were fractionated according to Watabe and colleagues (Watabe et al, 1992), separated on SDS-PAGE and transferred to polyvinylidene difluoride membranes (Millipore, Billerica, MA, USA). The fragment bands were analyzed for their N-terminal amino acid sequences with an Applied Biosystems Procise 492HT protein sequencer.…”
Section: Purification Of Myosin and N-terminal Amino Acid Sequencingmentioning
confidence: 99%
“…Studies with fully activated skinned fibers found that maximum tension and shortening speed increased at low temperatures in both fast and slow muscles following a period of cold acclimation (Johnston et al, 1985). We have shown that changes in the expression of MYH isoforms play a key role in the plasticity of myofibrillar ATPase activity and contractile properties with temperature acclimation (Hwang et al, 1990;Watabe et al, 1992Watabe et al, , 1995Guo et al, 1994). Three distinct MYH DNAs were cloned from the fast myotomal muscle of carp acclimated to either 10°C or 30°C for a minimum of 6·weeks (Imai et al, 1997;Hirayama and Watabe, 1997).…”
Section: Introductionmentioning
confidence: 99%